An Underground Building at Midhouse, Orkney; Two Urns found at Lintlaw, Berwickshire; and the Excavation of a Cairn at Drumelzier, Peeblesshire - Craw, John Hewat (Proceedings of the Society of Antiquaries of Scotland, 1931)
The structure at Midhouse was a stone-built chamber with passageway. No artefacts were recovered. At Lintlaw two inverted urns containing cremated human bone were found in close proximity to a cist containing charcoal and a fragment of burnt bone. The cairn at Drumelzier covered seven cists. Artefacts included six urns, cremated human bone, worked flint, a jet armlet and a whetstone. A slab with carved ring markings was also found.